2009
DOI: 10.1016/j.febslet.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Natively unfolded nucleic acid binding P8 domain of SeMV polyprotein 2a affects the novel ATPase activity of the preceding P10 domain

Abstract: Edited by Peter BrzezinskiKeywords: P10 P8 Natively unfolded Nucleic acid binding ATPase Sesbania mosaic virus a b s t r a c t Open reading frame (ORF) 2a of Sesbania mosaic virus (SeMV) codes for polyprotein 2a (Membrane anchor-protease-VPg-P10-P8). The C-terminal domain of SeMV polyprotein 2a was cloned, expressed and purified in order to functionally characterize it. The protein of size 8 kDa (P8) domain, like viral protein genome linked (VPg), was found to be natively unfolded and could bind to nucleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…In a broader sense, the interaction of P1 with the genome-bound VPg and P10 was considered as a cue of an active transport of viral RNA complex facilitated by P1 acting as a MP. The energy needed for that process was suspected to come from the hydrolysis of ATP by SeMV P10, as P1 itself did not show any ATPase activity [ 99 , 100 ]. When expressed in E. coli , SeMV P1 appeared to be in large soluble aggregates, characteristic of several MPs [ 98 ].…”
Section: P1 In Viral Movement and Suppression Of Rna Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a broader sense, the interaction of P1 with the genome-bound VPg and P10 was considered as a cue of an active transport of viral RNA complex facilitated by P1 acting as a MP. The energy needed for that process was suspected to come from the hydrolysis of ATP by SeMV P10, as P1 itself did not show any ATPase activity [ 99 , 100 ]. When expressed in E. coli , SeMV P1 appeared to be in large soluble aggregates, characteristic of several MPs [ 98 ].…”
Section: P1 In Viral Movement and Suppression Of Rna Silencingmentioning
confidence: 99%
“…The C-terminal part of P2a is not conserved. It was demonstrated that SeMV P2a C-terminus contains an RNA-binding domain (P10) and a novel ATPase domain (P8) [ 100 ]. The C-terminal part of the polyprotein P2ab consists of the motifs characteristic for an RdRp.…”
Section: Proteolytic Processing Of Polyproteinmentioning
confidence: 99%
“…It is not clear whether it has a functional role, or if it is only the byproduct of proteolytic cleavage. Recent studies using purified ORF2a encoded C-terminal fragments from SeMV, demonstrated ATPase and nucleic acid binding activity for the corresponding recombinant proteins (Nair and Savithri, 2010a). Such properties are characteristic, for example, for plant virus-encoded helicases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that the protease-VPg (Δ70 Pro-VPg) but not the protease (Δ70 Pro) alone is active [15]. Similarly, the ATPase activity of p10 domain was stimulated by the p8 domain present at its C-terminus [14]. Further, VPg-RdRp is the predominant intermediate of 2ab processing in E.coli [11].…”
Section: Introductionmentioning
confidence: 99%